A difference equation and a sum

Calculus Level 3

Let y k y_k be a sequence, where y 2 = 1 4 y_2 = \dfrac{1}{4} , and

y k + 1 = 1 4 ( 3 y k + 1 ) , k 2 y_{k+1} =\dfrac{1}{4}( 3 y_{k} + 1), \hspace{6pt} k \ge 2

And let x k x_k be another sequence defined explicitly by x 2 = 1 4 x_2 = \dfrac{1}{4} , and x k + 1 = 1 4 ( 1 y k ) , k 2 x_{k+1} = \dfrac{1}{4} (1 - y_k ) , \hspace{6pt} k \ge 2

Find k = 2 k x k \displaystyle \sum_{k=2}^{\infty} k x_k

3 4 5 6

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Hosam Hajjir
Apr 24, 2021

First, we'll find the solution to the difference equation, which can be written as

y k + 1 3 4 y k = 1 4 y_{k+1} - \dfrac{3}{4} y_k = \dfrac{1}{4}

This is a simple first order difference equation whose solution is known to be

y k = A ( 3 4 ) k + B y_k = A \left( \dfrac{3}{4} \right) ^k + B

where the constants A A , B B are yet to be determined.

Plugging in this form into the difference equation yields,

A ( 3 4 ) k + 1 + B 3 4 ( A ( 3 4 ) k + B ) = 1 4 A \left( \dfrac{3}{4} \right) ^{k+1} + B - \dfrac{3}{4} \left( A \left( \dfrac{3}{4} \right) ^k + B \right) = \dfrac{1}{4}

From which, B = 1 B = 1

To find A A we use the initial conditions.

y 2 = 1 4 = A ( 3 4 ) 2 + 1 y_2 = \dfrac{1}{4} = A \left( \dfrac{3}{4} \right) ^2 + 1

from which A = 4 3 A = - \dfrac{4}{3}

Therefore, y k = 1 ( 3 4 ) k 1 y_k = 1 - \left( \dfrac{3}{4} \right) ^{k-1}

Next, we'll find x k x_k . Substituting y k y_k into x k + 1 = 1 4 ( 1 y k ) x_{k+1} = \dfrac{1}{4} ( 1 - y_k ) gives us

x k + 1 = 1 4 ( 3 4 ) k 1 x_{k+1} = \dfrac{1}{4} \left( \dfrac{3}{4} \right) ^{k-1}

so that,

x k = 1 4 ( 3 4 ) k 2 x_{k} = \dfrac{1}{4} \left( \dfrac{3}{4} \right) ^{k-2}

Now, we want to find the sum,

S = k = 2 k x k = 1 4 k = 2 k ( 3 4 ) k 2 = 1 4 j = 0 ( j + 2 ) ( 3 4 ) j S = \displaystyle \sum_{k=2}^{\infty} k x_k = \dfrac{1}{4} \sum_{k=2}^{\infty} k \left( \dfrac{3}{4} \right) ^{k-2} =\dfrac{1}{4} \sum_{j=0}^{\infty} (j+2) \left( \dfrac{3}{4} \right) ^{j}

Simplifying,

S = 1 4 ( 2 j = 0 ( 3 4 ) j + j = 0 j ( 3 4 ) j ) S =\displaystyle \dfrac{1}{4} \left( 2 \sum_{j=0}^{\infty}\left( \dfrac{3}{4} \right) ^{j} + \sum_{j=0}^{\infty} j \left( \dfrac{3}{4} \right) ^{j} \right)

The first sum is just a geometric series sum and evaluates to 1 1 3 4 = 4 \dfrac{1}{1 - \frac{3}{4} } = 4 . The second sum is handled as follows

j = 0 j ( 3 4 ) j = 3 4 j = 1 j ( 3 4 ) j 1 \displaystyle \sum_{j=0}^{\infty} j \left( \dfrac{3}{4} \right) ^{j} = \dfrac{3}{4} \sum_{j=1}^{\infty} j \left( \dfrac{3}{4} \right) ^{j-1} = 3 4 d d s ( j = 1 s j ) s = 3 4 = 3 4 d d s ( s 1 s ) s = 3 4 = 3 4 ( 1 ( 1 s ) 2 ) s = 3 4 = 3 4 × 16 = 12 \displaystyle =\dfrac{3}{4} \dfrac{d}{ds} \left( \sum_{j=1}^{\infty} s^j \right) \bigg|_{s = \frac{3}{4} } = \dfrac{3}{4} \dfrac{d}{ds} \left( \dfrac{s}{1 - s} \right) \bigg|_{s = \frac{3}{4}} = \dfrac{3}{4} \left( \dfrac{1}{(1 - s)^2} \right) \bigg|_{s = \frac{3}{4} } = \dfrac{3}{4} \times 16 = 12

Putting it all together,

S = 1 4 ( 2 × 4 + 12 ) = 5 S = \dfrac{1}{4} ( 2 \times 4 + 12 ) = \boxed{5}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...